Pengaruh Social Factor dan Attitude terhadap Purchase Intention Pakaian Bekas Import : (Studi Kasus Pada Generasi Z Di Kabupaten Kolaka) - Nur Vebriani; Andry Stepahnie Titing; Ismanto Ismanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research aims to determine: (1) The influence of social factors on the purchase intention of imported second-hand clothing (Case study of Generation Z in Kolaka Regency) and (2) The influence of Attitude on Purchase Intention of Imported used clothing (Case study of Generation Z in Kolaka Regency). This research is quantitative research with an explanatory research model using a questionnaire as the instrument. The population in this study were all consumers of imported used clothing with a sample size of 75 respondents using observation, documentation and questionnaire techniques. Data collection techniques are primary data and secondary data. Research instrument testing uses validity and reliability tests with SPSS 25. Research data analysis techniques use the Structural Equation Modeling (SEM-PLS) method with SmartPLS 3.0. Based on the research results, it is known that social factors have a positive and significant effect on purchase intention. This is proven by the t-count or t-statistic which is 2.519 which is higher than the t-table value > 1.666. With P-values ​​0.006. Meanwhile, attitude also has a positive and significant effect on purchase intention because the t-count or t-statistic value of 6.371 is higher than the t-table value of >1.666 with P-values ​​of 0.000. So social factors and attitude have a positive and significant effect on purchase intention by 82.3%.